Kinematic Comparisons of the Shakehand and Penhold Grips in Table Tennis Forehand and Backhand Strokes when Returning Topspin and Backspin Balls - Xia, Rui (J Sports Sci Med, 2020)
Identifying the factors associated with table tennis performance may provide training information for competitive athletes and guide the general population for active participation. The purpose was to compare the joint, racket, and ball kinematics between the shakehand and penhold grips in table tennis forehand and backhand strokes when returning topspin and backspin balls in advanced male players. Nine penhold-grip players and 18 matched shakehand-grip players performed forehand and backhand strokes when returning topspin and backspin balls using their habitual grip styles, while the kinematics of the trunk, upper extremities, racket, and ball were collected. Racket angles were calculated as the relative motion of the racket to the forearm. For the forehand strokes, no significant differences were observed for ball or racket velocities between the two grips. The shakehand grip tended to demonstrate greater shoulder external rotation angles compared to the penhold grip. The shakehand grip resulted in racket flexion angular velocity compared to racket extension velocity for the penhold grip. For the backhand strokes, greater ball and racket velocities were observed for the shakehand grip. The shakehand grip generally demonstrated decreased final trunk left rotation angles, increased trunk right rotation angular velocities, decreased final shoulder abduction angles, increased shoulder adduction angular velocities, and increased forearm supination angular velocities. The two grips demonstrated similar peak racket and ball velocities but different shoulder rotation range of motion and racket motion in forehand strokes. The penhold grips resulted in decreased peak racket and ball velocities in backhand strokes, likely due to its decreased shoulder, elbow, and forearm motion and less aligned longitudinal axes between the racket and forearm. These findings may help understand the dominance of the shakehand grip over the penhold grip in elite athletes and provide information for grip selection, technique improvements, and exercise training.